Management of short‐bowel syndrome: A survey of unmet educational needs among healthcare providers. Issue 8 (24th May 2022) - Belcher, Emily; Mercer, David; Raphael, Bram P.; Salinas, Gregory D.; Stacy, Sylvie; Tappenden, Kelly A.
Abstract: Background: Management of short‐bowel syndrome with intestinal failure (SBS‐IF) is complex and requires a multidisciplinary approach. Because of the rarity of SBS‐IF, healthcare professionals (HCPs) often lack clinical experience with the disease and may benefit from education regarding SBS‐IF and its management. This study identified unmet educational needs related to the management of patients with SBS‐IF. Methods: This was a prospective, web‐based survey (December 2019–January 2020) in which a series of clinical questions were posed to US HCPs after presenting three standardized SBS‐IF cases to assess current practice patterns. HCPs were then asked a series of questions to identify potential knowledge gaps and unmet educational needs relating to SBS‐IF management. Results: Overall, 558 HCPs completed the survey, with 12%–38% having a formal SBS‐IF multidisciplinary team currently available to make treatment decisions within their institution. Clinicians involved in care included gastroenterologists (93%), registered dietitians (79%), gastroenterology nurse practitioners and physician assistants (37%), registered nurses (43%), social workers (45%), and psychologists/psychiatrists (27%). There was underuse of published guidelines and limited understanding of the course of intestinal adaptation. Responses to the clinical scenarios highlighted disparities in SBS‐IF care delivery, including diagnosis, management goals, medications prescribed, and nutrition practices. Conclusions: Future SBS‐IF educational interventions for HCPs should aim to improve awareness and understanding of the disease, facilitate timely diagnosis, and standardize management practices to ensure patients receive optimal interdisciplinary care as widely as possible.